Learning-facilitated synaptic plasticity occurs in the intermediate hippocampus in association with spatial learning - Kenney, Jana; Manahan-Vaughan, Denise (Frontiers in Synaptic Neuroscience, 2013)
The dorsoventral axis of the hippocampus is differentiated into dorsal, intermediate and ventral parts. Whereas the dorsal part is believed to specialize in processing spatial information, the ventral may be equipped to process non-spatial information. The precise role of the intermediate hippocampus is unclear, although recent data suggests it is functionally distinct, at least from the dorsal hippocampus. Learning-facilitated synaptic plasticity describes the ability of hippocampal synapses to respond with robust synaptic plasticity (>24h) when a spatial learning event is coupled with afferent stimulation that would normally not lead to a lasting plasticity response: In the dorsal hippocampus novel space facilitates robust expression of LTP, whereas novel spatial content facilitates LTD. We explored whether the intermediate hippocampus engages in this kind of synaptic plasticity in response to novel spatial experience. In freely moving rats, high-frequency stimulation at 200Hz (3 bursts of 15 stimuli) elicited synaptic potentiation that lasted for at least 4h. Coupling of this stimulation with the exploration of a novel holeboard resulted in long-term potentiation (LTP) that lasted for over 24h. Low frequency afferent stimulation (1Hz, 900 pulses) resulted in short-term depression (STD) that was significantly enhanced and prolonged by exposure to a novel large orientational (landmark) cues, however LTD was not enabled. Exposure to a holeboard that included novel objects in the holeboard holes elicited a transient enhancement of STD of the population spike but not field EPSP, and also failed to facilitate the expression of LTD. Our data suggest that the intermediate dentate gyrus engages in processing of spatial information, but is functionally distinct to the dorsal dentate gyrus. This may in turn reflect their assumed different roles in synaptic information processing and memory formation.